Closing yield gaps in Ethiopia: Leveraging data-driven approaches to optimize fertilizer use and soil health - Tamene, Lulseged; Mesfin, Tewodros; Tibebe, Degefie; Abera, Wuletawu; Desta, gizaw; Liben, Feyera; Agegnehu, Getachew; Tigabie, Abiro; Legesse, Gizachew; Chernet, Meklit; Ebrahim, Mohammed; Tilaye, Asmalu; et al. (2024)
Ethiopia faces substantial yield gaps in cereal production, with average yields of staple crops falling significantly short of their potential. A key issue is the persistent use of blanket fertilizer recommendations, which overlook local soil variability and environmental conditions. This paper explores the transition towards climate-smart, site-specific, and data-driven fertilizer recommendations as a transformative approach for Ethiopian agriculture. Leveraging advanced agricultural data, big data analytics, and machine learning, the Alliance of Bioversity and CIAT, along with ICRISAT and key partners, have developed and piloted advanced decision support tools (DSTs). These tools are designed to optimize nutrient application and deliver tailored agronomic advice adapted to local contexts. The Ethiopian government’s endorsement of these innovative approaches demonstrates their potential to significantly enhance productivity and promote sustainable farming practices. However, efforts remain fragmented, as these research institutions deploy separate tools without a unified DST framework for national application. To overcome this challenge, a harmonized DST framework has been proposed, integrating multiple tools into a cohesive system. This collaborative initiative is reshaping Ethiopia's agricultural landscape and aligns with government priorities for the digital delivery of customized agronomic solutions and extension services. The active participation of the CGIAR’s Excellence in Agronomy Initiative (EiA), alongside national and regional research institutes, has been instrumental in building the data ecosystem, performing analytics, generating advisory content, and validating the tools in field conditions. The harmonized DST framework is currently undergoing extensive field testing by the Ethiopian Institute of Agricultural Research, reaching over 2,500 farmers’ fields for key cereal crops. This initiative marks a departure from traditional blanket fertilizer strategies, moving towards site-specific, data-driven agronomic recommendations delivered through agile communication channels. By improving fertilizer recommendations and enhancing soil health, this initiative aims to close cereal yield gaps and promote sustainable crop production. It offers tailored, localized solutions that address Ethiopia’s diverse agricultural landscape, empowering farmers and enabling impact at scale. The approach also strengthens resilience against environmental challenges, setting a precedent for similar collaborative efforts across sub-Saharan Africa. Ultimately, this paper highlights the importance of coordinated partnerships and the integration of innovative technologies to effectively close yield gaps, enhance soil health, and ensure food security through a more sustainable and adaptive agricultural system that meets future demands in a changing climate.